PL03.2.A Radiotherapy is associated with a deletion signature that contributes to poor outcomes in glioma patients. (9th September 2021) - Kocakavuk, E; Anderson, K J; Varn, F S; Johnson, K C; Amin, S B; Sulman, E P; Lolkema, M P; Barthel, F P; Verhaak, R G W
Abstract: BACKGROUND: Diffuse gliomas are highly aggressive brain tumors that invariably relapse despite treatment with chemo- and radiotherapy. Treatment with alkylating chemotherapy can drive tumors to develop a hypermutator phenotype. In contrast, the genomic effects of radiation therapy (RT) remain largely unknown. MATERIAL AND METHODS: We analyzed the mutational spectra following treatment with RT in whole genome or exome sequencing data from 190 paired primary-recurrent gliomas from the Glioma Longitudinal Analysis (GLASS) dataset and 3693 post-treatment metastatic tumors from the Hartwig Medical Foundation (HMF). RESULTS: We identified a significant increase in the burden of small deletions following radiation therapy that was independent of other factors ( P = 3e-03, multivariable log-linear regression). These novel deletions demonstrated distinct characteristics when compared to pre-existing deletions present prior to RT-treatment and deletions in RT-untreated tumors. Radiation therapy-acquired deletions were characterized by a larger deletion size (GLASS and HMF, P = 1.5e-04 and P = 6e-16, respectively; Mann-Whitney U test), an increased distance to repetitive DNA elements ( P < 2.2e-16, Kolmogorov-Smirnov test) and a lack of microhomology at breakpoints ( P = 6.6e-05, paired Wilcoxon signed-rank test). Furthermore, mutational signature analysis confirmed the distinct genomic characteristics of RT-associated deletions when compared to deletions arising via homologous recombination deficiency or microsatellite instability. These observations suggested that canonical non-homologous end joining (c-NHEJ) was the preferred pathway for DNA double strand break repair of RT-induced DNA damage. Furthermore, RT resulted in frequent chromosomal deletions and significantly increased frequencies of CDKN2A homozygous deletions in IDHmut glioma ( P = 1.9e-05, Fisher's exact test). Finally, a high burden of RT-associated deletions was associated with worse clinical outcomes (GLASS and HMF, P = 3.4e-02 and P < 1e-04, respectively; log-rank test). CONCLUSION: Our results collectively suggest that effective repair of RT-induced DNA damage is detrimental to patient survival and that inhibiting c-NHEJ may be a viable strategy for improving the cancer-killing effect of radiotherapy. Furthermore, CDKN2A homozygous deletion at recurrence may be leveraged as a promising clinical biomarker of RT-resistance in IDHmut glioma. Taken together, the identified genomic scars as a result of RT reflect a more aggressive tumor with increased levels of resistance to follow up treatments.